El teletrabajo como mecanismo paradigmático del poder en las sociedades de control modernas (Sección Abierta) - Andrade Ortiz, Edison Ricardo (2022)
During the gradual massification and incorporation of multiple information and communication technologies into people’s daily lives, the labor sector has been no exception. Since, with the disruptive adoption of teleworking across the board at public and private levels, this is seen as a shocking measure to combat the economic ravages of COVID-19. It imprints particular circumstances concerning the elements that strengthen the behaviors of disciplining, subjugation and domination; from the digital tools on the so-called teleworkers today. Being the central theme of this research article. This article aims to evaluate the role of teleworking in today’s societies of control, starting from Foucault’s disciplinary societies, then involving Deleuze’s societies of control, and finally contrasting it with Byung-Chul Han’s Big Data. The analysis is developed from texts and articles that study telework, disciplinary societies, and societies of control in the postmodern era in depth. These themes are worked on by authors from the sciences of law, sociology, and philosophy, who have managed to catalyze their knowledge and efforts to give shape to this new phenomenon.